Metode Peningkatan Akurasi pada Sensor TDS Berbasis Arduino untuk Nutrisi Air Menggunakan Regresi Linier - Dhodit Rengga Tisna; Berlian Juliartha Martin Putra; Tamara Maharani; Hasnira Hasnira (Politeknik Negeri Batam, 2022)
Water quality has an important role in the field of aquaculture. One of the factors that determine water quality is the level of TDS (Total Disolved Solid). Therefore, a TDS meter that has precise accuracy is needed to be able to accurately measure the quality of various types of water. In this study developed a prototype capable of measuring TDS levels in water. This prototype consists of a TDS sensor device, Arduino UNO and an LCD to display the results of the measured water quality readings. So that the accuracy read by the prototype is able to match the commercial TDS meter, the researchers used a linear regression algorithm to be included in the Arduino TDS program. The results of the experiment show that the accuracy of the TDS prototype which was originally 77% increased to 98.3%, is almost close to precision with commercial TDS meters in general.